2018
DOI: 10.1111/jog.13745
|View full text |Cite
|
Sign up to set email alerts
|

The level of vitamin D using the LC–MS/MS method and related factors in healthy Korean postmenopausal women

Abstract: Both 25(OH)D and total 25(OH)D were negatively correlated with PTH, a bone formation marker (alkaline phosphatase) and percent body fat. Both 25(OH)D and total 25(OH)D were positively correlated with a bone resorption marker (C-terminal cross-linked telopeptides of type I collagen), ESR and Apo A-I after multiple regression analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In our study, a large percentage of the population presented 25-OH-D levels below the reference values when analyzed by LC-MS/MS. Authors such as Park et al [43] analyzed 25-OH-D levels by LC-MS/MS in a population of postmenopausal women, and recorded the same high prevalence of vitamin D deficiency (82%) as in our study. This confirmed that despite use of the gold standard for the analytical determination of vitamin D, the levels of this vitamin were low.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, a large percentage of the population presented 25-OH-D levels below the reference values when analyzed by LC-MS/MS. Authors such as Park et al [43] analyzed 25-OH-D levels by LC-MS/MS in a population of postmenopausal women, and recorded the same high prevalence of vitamin D deficiency (82%) as in our study. This confirmed that despite use of the gold standard for the analytical determination of vitamin D, the levels of this vitamin were low.…”
Section: Discussionsupporting
confidence: 82%
“…We used LC-MS/MS to test serum 25(OH) D concentrations in current study. LC-MS/MS is widely accepted in clinical laboratories to differentiate between vitamin-D deficiency and sufficiency, because of its excellent analytical specificity and sensitivity [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an inverse association was found between vitamin D status and fat mass. However, the weakness of this association might be explained by the presence of numerous factors which modulate fat mass, such as ethnicity, age [46], sun exposure habit, diet, and the season of the year in which the samples were taken, which can mean that even though a woman has a high fat mass, its influence on vitamin D status can lose strength [47,48]. In our study, due to the limited sample size, we could not control for some of these confounding factors.…”
Section: Discussionmentioning
confidence: 99%